Parametric study of buckling and post-buckling behavior for an aluminum hull structure of a high-aspect-ratio twin hull vessel. (February 2020) - Soleimani, Ebrahim; Tabeshpour, Mohammad Reza; Seif, Mohammad Saeed
Metal plates are essential parts of structures such as ship hulls and offshore oil platforms. These plates are typically under compressive axial forces. Hence, one of the main mechanisms for failure and collapse of such structures is buckling of plates. Thus, for safe and secure design, buckling strength of plates should be evaluated. Finite element analysis techniques are perfect tools for this purpose because of the accuracy and flexibility for performing simulations with different variables. In this study, the strength of aluminum plates has been studied using finite element analysis software and it was tried to study the influence of variables such as initial imperfections, plate thickness and aspect ratio on plate strength. It was found that increase in the imperfection magnitude leads to a decrease in the strength of the plate. This is mostly noticed in thin plates because of the plate's stiffness reduction. Although the plate's aspect ratio has a slight effect on strength, it has a considerable impact on the failure mechanism. In order to study a combination of plates and stiffeners buckling behavior, part of a high-aspect-ratio twin hull vessel hull structure is assessed under bending moment. It is observed that longitudinal stiffeners at the bottom of the hull in linear analysis undergo the maximum stress, while in non-linear analysis, the maximum stress is spread along with the structure of the deck and bottom, and neutral axis tolerates the minimum stress.